An essay on precision in morphometric measurements in anurans: inter-individual, intra-individual and temporal comparisons - Bernal, Manuel Hernando; Clavijo, Jairo Alfonso (Zootaxa, 2009)
Morphometric comparisons among specimens continue being an important tool for biological and taxonomical studies and are indispensable for the description of new species. However, there are few works that have been done to compare the precision of the measurements that different investigators take in live or preserved animals with different body sizes and time of preservation. Herein we evaluate statistically this information. The results indicate that there are significant differences among the measurements taken by different people (inter-individual comparisons), but not within each of them (intra-individual comparisons). Also, there are temporal differences in the morphometric measurements among living animals, freshly preserved specimens and specimens after five months of preservation. These results demonstrate that morphometric measurements must be made by just one person and that for any morphometric analysis it is important to keep in mind the preservation time differences of the animals in the museums.